Community Engagement: School and Family Partnerships to Support Mutual Learning - Hurtado, Carolee (Allies for Education, 2018)
Community engagement in schools that place parent voice at the forefront? Can mathematics be a place for restorative practices? In this article, we share our journey for a family-school partnerships modeled from the visioning of parents who dared to dream differently.